2015
DOI: 10.1007/s40544-015-0080-8
|View full text |Cite
|
Sign up to set email alerts
|

Microscale study of frictional properties of graphene in ultra high vacuum

Abstract: Abstract:We report on the frictional properties of epitaxial graphene on SiC in ultra high vacuum. Measurements have been performed using a microtribometer in the load regime of 0.5 to 1 mN. We observed that a ruby sphere sliding against graphene results in very low friction coefficients ranging from 0.02 to 0.05. The friction and also the stability of the graphene layer is higher than that under similar conditions in ambient conditions. The friction shows a load dependence. Finally it was found that graphene … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 25 publications
1
26
0
Order By: Relevance
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…As illustrated in Figure a–d, three domains (SLG, BLG, and Cu) showing different friction responses in each panel can be clearly distinguished. Friction forces of both SLG and BLG domains are much smaller than that of bare copper substrate since an ideal graphene film is atomically smooth and has no dangling bond, resulting in low shear strength . Friction force of SLG is larger than that of BLG, which is consistent with previous literature .…”
Section: Resultssupporting
confidence: 90%
“…[1,2] It can be used as solid, atomic-thick coating or as colloidal liquid lubricant. Its high strength, chemical stability and easy shear capability make it very appealing for a wide range of tribological applications, as revealed by the increasing number of experimental [3][4][5][6][7][8][9][10][11][12][13][14][15] and theoretical studies[16-28] on graphene friction. Recent experimental findings, in particular, revealed that graphene posses a great potential as solid lubricant not only for nano-scale, but also for macro-scale applications.…”
mentioning
confidence: 99%
“…Despite great advances in science and technology and remarkable research progress on friction, the current understanding of friction and lubrication phenomena is macroscopic. Owing to the development of micromechanical devices, macroscopic tribology theory has become obsolete, and the characteristics of friction at the microscale have been extensively investigated [25,26]. Tribology has also followed this developmental trend and has gradually evolved into nanotribology.…”
Section: Nanoscale Friction Mechanism Of 2d Materialsmentioning
confidence: 99%